Expanding the phenotypic spectrum of acro-cardio-facial syndrome (ACFS): Exclusion of P63 mutation - Pranoot Tanpaiboon (2018)
Acro-cardio-facial syndrome (ACFS) is a rare autosomal recessive congenital malformation syndrome; consistent features include ectrodactyly, cleft lip/palate with minor facial anomalies, genital abnormalities, mental retardation, and growth retardation. Five cases have been reported. We report on a new patient with ACFS syndrome. In addition to the characteristic features of ACFS, the reported patient also has mild scoliosis, hemivertebrae and subclinical hyperthyroidism. These additional features may expand the phenotypic spectrum of the syndrome. © 2009 Wiley-Liss, Inc.